2015
DOI: 10.1038/bmt.2015.7
|View full text |Cite
|
Sign up to set email alerts
|

Reduced-intensity conditioned allogeneic SCT in adults with AML

Abstract: AML is currently the most common indication for reduced-intensity conditioned (RIC) allo-SCT. Reduced-intensity regimens allow a potent GVL response to occur with minimized treatment-related toxicity in patients of older age or with comorbidities that preclude the use of myeloablative conditioning. Whether RIC SCT is appropriate for younger and more standard risk patients is not well defined and the field is changing rapidly; a prospective randomized trial of myeloablative vs RIC (BMT-CTN 0901) was recently cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 152 publications
(174 reference statements)
1
36
0
Order By: Relevance
“…3,4,11,12 Reduced-intensity conditioning (RIC) regimens have further extended the use of allogeneic HCT to older patients and those with significant pre-transplant comorbidities. 9,13,14 Several previous studies comparing the clinical outcomes of RIC and MAC regimens after matched related or unrelated donor HCT in AML have shown similar outcomes; [13][14][15][16] however, it is unknown in patients receiving mismatched unrelated donor (MM-URD) HCT. Therefore, we explored whether there were outcome differences for adults with AML after RIC or MAC regimens in the setting of MM-URD HCT using data reported to the European Society for Blood and Marrow Transplantation (EBMT).…”
Section: Introductionmentioning
confidence: 99%
“…3,4,11,12 Reduced-intensity conditioning (RIC) regimens have further extended the use of allogeneic HCT to older patients and those with significant pre-transplant comorbidities. 9,13,14 Several previous studies comparing the clinical outcomes of RIC and MAC regimens after matched related or unrelated donor HCT in AML have shown similar outcomes; [13][14][15][16] however, it is unknown in patients receiving mismatched unrelated donor (MM-URD) HCT. Therefore, we explored whether there were outcome differences for adults with AML after RIC or MAC regimens in the setting of MM-URD HCT using data reported to the European Society for Blood and Marrow Transplantation (EBMT).…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Moreover, outcomes for unrelated donor HCT after RIC regimens appear comparable to those seen with sibling donor RIC HCT. 3,[13][14][15] Here we report on transplant outcomes after related or unrelated donor BMT (n=837) versus PBSCT (n=9011) in the setting of reduced intensity conditioning for the treatment of adults with acute leukemia using data reported to the ALWP of the EBMT from 2000 to 2012.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Furthermore, following the introduction of reduced intensity conditioning (RIC) regimens, individuals with co-morbidities and those 65 years of age and older are now eligible to undergo HCT. [3][4][5] The use of peripheral blood stem cells (PB) has largely replaced bone marrow (BM) as the main stem cell source for HCT in adults with hematologic malignancies. 1 However, limited data are available on the impact of the stem cell source (related or unrelated donor) in the setting of RIC HCT, [6][7][8][9][10] including our small previous European Group for Blood and Marrow Transplantation (EBMT) series.…”
Section: Introductionmentioning
confidence: 99%
“…2 In an attempt to extend the use of allo-HCT to older patients and those with medical comorbid conditions, several groups of investigators have carried out allo-HCT after reduced intensity (RIC) or truly nonmyeloablative conditioning regimens. 4,5 These regimens rely on graft-versus-AML effects rather than on chemo/radiotherapy for tumor eradication. 3,6 Remarkably, a recent study by the HOVON/SAKK group demonstrated that RIC/nonmyeloablative allo-HCT improved overall survival (OS) in older (60 years of age or older) patients with intermediate or high-risk AML in comparison with those not transplanted.…”
mentioning
confidence: 99%